Sonosalpingography - Malhotra, Narendra; Malhotra, Jaideep; Mittal, Sakshi; Singh, Amita (Nepal Journal of Obstetrics and Gynaecology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–>doi:10.3126/njog.v1i2.2405 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 71-73 Nov-Dec 2006